THE EFFECT AUDIT COMMITTEE AND INDEPENDENT COMMISSIONER ON EARNINGS MANAGEMENT - Asrie Dyah; E. Novita; Nikmah Nikmah (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aimed to examine the effect of audit committee, independent commissioner  on earnings management. The sample in this study are banking   in   Southeast Asia of period 2017- 2021. The data used in this study is secondary data obtained from the financial data at  banking  website.  The number  of samples  in  this  study are 52  banks.  Data  analysis  was  performed  with  multiple regression analysis using SPSS version 23. The result showed that audit committee, independent commisioners has no effect on earnings management.  Key Words: Earnings Management, Audit Comitte, Independent Commisioners